PENDEKATAN FILSAFAT DALAM KAJIAN ISLAM: TEORI DAN PRAKTIK - Nurul Ainiy (Universitas Islam Malang, 2022)
In historical records, philosophical principles and Islamic concepts do not always compatible. The characteristics of philosophy which always question the truth of everything and Islamic principles that hold fast to the truth of revelation as the ultimate truth often lead to conflict. Along with the development of science, Muslim scientists found that philosophy as a scientific methodology can coexist with religious knowledge without contradicting the truth values that have been established in Islam. This study aims to examine more deeply the concept of Philosophy theoretically as a scientific approach as well as the implementation steps in Islamic studies. This study uses qualitative descriptive method with the type of library research. The data analysis technique consists of several steps: 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results show that the philosophical approach in Islamic studies can be implemented using several techniques, including through relativism, realism, contextualism, and historical perspectives, within the scope of ontology, epistemology, or axiology. Examples of the implementation of philosophical-based Islamic studies that have been carried out include conceptual studies of Islamic education in the socio-cultural perspective, comparative studies of Islamic and Western perspective education, and applicative studies of the reconstruction of learning epistemology.